Learn by example: MATLAB app design - Harun, Nor Hazlyna; Hambali, Hamirul ’Aini; Hassan, Mohamad Ghozali; Karim, Khairah Nazurah (UUM Press, 2017)
MATLAB App Designer is a feature that allows MATLAB code to be packaged into an interactive software.The software can be shared on any computer without the trouble of having to install MATLAB or even knowing programming knowledge to be able to operate the software.This books provides hands on approach to guide learners in developing the software from scratch using MATLAB App Designer.It covers a wide variety on standard graphical component (radio button, tables, button, check boxes, sliders and many others) and how to utilize its properties and function in deploying end user software.Source code for all the example program can be studied and understand by student easily.This equips learners with the fundamental and required skills for developing the application on their own. Added that, the example code can be reusable with other case problem or application similar to the hands on example. The key to mastering any application development software is to practice, so that you are familiarize with the components and understand its properties and behavior.In simple word, knowing how each components work is essential. This is where this book benefits learner that needs to develop software application using MATLAB.